RESEARCH DATA MANAGEMENT IN LIBRARY: A BIBLIOMETRIC ANALYSIS OF THE PAST DECADE (2013-2023) - Zati Atiqah Mohamad Tanuri; Abd Latif Abdul Rahman; Zuraidah Arif (Journal of Islamic, Social, Economics and Development, 2023)
Research data management is an essential aspect of modern scientific research, and its importance has been increasingly recognized in recent years. With the growth of digital data and the demand for open science, the need for effective research data management practices has become more critical. Most academic research libraries are offering a variety of research data management services. The services are just expanded versions of conventional consulting or informative services, including assisting instructors and students in finding datasets or repositories. Conducting a bibliometric analysis of research data management can help address gap in the literature and provide a comprehensive overview of research trends in this field. The objectives of the paper are as follows: (1) to identify the research trends about research data management in library using bibliometric analysis; (2) to examines the clusters that include the co-occurrence of author keywords; (3) to produce a synthesised analysis of research trends on research data management in library, with particular attention to the geographic distribution of publications and authorship. This study reveals a bibliometric analysis of research data management in libraries as a theme in the current research trends and agenda. A total of 365 articles extracted from the Scopus database within the past 10 years, published from 2013 to 2023, were selected to be analyzed. The analysis of the academic work that was extracted throughout the search process was based on the following features; document and source type, subject area, most active source title, distribution of publications by countries, keyword analysis, and citation analysis.